Landslide susceptibility mapping of Noklak Town, Nagaland, North‐east India using bivariate statistical method. Issue 12 (25th September 2022) - Jamir, Mademshila; Chang, Chongpongnungba Nokendangba; Jamir, Imlirenla; Thong, Glenn T.; Walling, Temsulemba
Abstract : The increasing frequency of landslides has become a matter of concern in Nagaland, a north‐eastern state of India. Noklak town, the administrative headquarter of the Noklak district in the eastern part of Nagaland bordering Myanmar, is also affected by slope stability issues. A major landslide in 1980 caused major damage to parts of the township. The problem has grown in magnitude and influence over the last four decades, damaging an area of about 1.84 km 2 and several households. Slope movements have caused immense distress to the local populace by posing a constant threat to nearly one‐fourth of the town's built‐up area, roads, and cultivated tracts. Surface instability has also hampered India's Act East policy with South‐east Asian countries by disrupting the sole motorable route to the International Trade Centre at Dan (Pangsha), between India and Myanmar. A landslide susceptibility map (LSM) was generated using the Bivariate Yule coefficient (Yc) method. The LSM delineates the study area into three categories, with 23%, 23%, and 54% in high, moderate, and low susceptible zones, respectively. This was superimposed with elements such as buildings, population, roads, and cultivated tracts to assess the effects of landslides on the population and infrastructure. From the present study, it is estimated that 334 buildings, 1235 people, 2.99 km of roads, and 8 ha of cultivated landfall lie within the moderately and highly susceptible zones. Considering the rapid developmental activities that will ensue with the recent upgradation of the subdivision to that of the district, the data generated will be useful for urban sprawl and land use planning, to minimise and mitigate the loss of life and property due to landslides. Abstract : Quantitative methods have been observed to provide more realistic results in landslide susceptibility mapping, and the Bivariate statistical Yule's coefficient method is found to have rapid computation and easy processing of data as compared to other methods. LSM generated using this method delineates 23% of Noklak town under high susceptibility of landslides. Numerous pieces of evidence in the study area point to the major role of neotectonic activity in the slope stability of the region.